Bestimmung der linksventrikulären Strömungsgeschwindigkeiten mit der EinzelsondenRadiokardiographie in der Phase der Gleichverteilung - Pilz, U.; Engelmann, L.; Hofmann, T.; Pätzold, J. (Nuklearmedizin - NuclearMedicine, 1991)
A new procedure of extracting data from measurements by single-probe radionuclide ventriculography is presented which reduces the phase differences during summation of single-beat actions and permits the use of a greater number of single actions for summation. Sum curves so determined are better suited for measurements of ejection fractions, compliance and ventricular blood flow rates.